2021
DOI: 10.1049/cth2.12190
|View full text |Cite
|
Sign up to set email alerts
|

Robust control of pantograph‐catenary system: Comparison of 1‐DOF‐based and 2‐DOF‐based control systems

Abstract: Compared to control bandwidth, low-frequency uncertainties or disturbances like step signals can be well rejected by many methods having two-degree-of-freedom (2-DOF). Due to robustness constraint, technically more challenging is the rejection of medium frequencies, especially for bandwidth-limited systems. Here, the equivalent-input-disturbance (EID) approach is extended to deal with the main medium-frequency oscillation of a pantograph-catenary system. First, a general EID estimator is developed with a lowfr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The time-varying parameter perturbations of the system matrix and output matrix are considered in this paper. Many scenarios fall into this case [23].…”
Section: Configuration Of Geid-based Disturbance-rejection Control Sy...mentioning
confidence: 99%
“…The time-varying parameter perturbations of the system matrix and output matrix are considered in this paper. Many scenarios fall into this case [23].…”
Section: Configuration Of Geid-based Disturbance-rejection Control Sy...mentioning
confidence: 99%
“…The works of these authors deserve attention when considering the effect of vehicle track excitations in conjunction with a spatial contact model that accounts for the interaction between the contact wire and the pantograph strip (Song, et al, 2021b). Several researchers have reported that mathematical modeling proved to be an effective approach in capturing the complex dynamic behavior of the pantograph system because of the high cost of field testing (Pham et al, 2022;Song and Li, 2021;Yu et al, 2021). However, it is found that the dynamic behavior of the pantograph system is limited when vehicle-track disturbances are considered.…”
Section: Introductionmentioning
confidence: 99%